2014
DOI: 10.4172/2375-446x.1000116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Bacterial Haemorrhagic Septicemia Disease of Cyprinus carpio and Channa striatus

Abstract: Bacterial Hemorrhagic Septicemia (BHS) was found affecting Cyprinus carpio and Channa striatus. Bacteriological examination and artificial infection trials were carried out on these fishes. Hematological examination showed substantial decline in the number of erythrocytes and lymphocytes, increase in the number of granulocytes and significant loss in the amount of hemoglobin. Histopathological examination suggested that the affected part of the skin had got completely destroyed. The peripheral area of the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…If water is deficient in O 2 as a result of algal bloom, high stocking density or stagnant water, continuous accumulation of CO 2 can contribute to inactivate the respiratory apparatus and develop stress among fishes. The diseased fishes in the pond exhibited abnormal behavior in swimming, orientation, decreased activity, refusal of feed and swimming very sluggishly were similar to one of the studies conducted by Parvez and Mudarris (2014). These abnormal changes in behavior of fish may correspond to pathogenic microorganisms as well (Rehman et al, 2017).…”
Section: Methodssupporting
confidence: 60%
“…If water is deficient in O 2 as a result of algal bloom, high stocking density or stagnant water, continuous accumulation of CO 2 can contribute to inactivate the respiratory apparatus and develop stress among fishes. The diseased fishes in the pond exhibited abnormal behavior in swimming, orientation, decreased activity, refusal of feed and swimming very sluggishly were similar to one of the studies conducted by Parvez and Mudarris (2014). These abnormal changes in behavior of fish may correspond to pathogenic microorganisms as well (Rehman et al, 2017).…”
Section: Methodssupporting
confidence: 60%
“…These findings might be the first report from Ethiopian, this is because very limited Cyprinus spps distribution among fish producing Lakes that indicated no study done on these fish species in Ethiopia. But from different countries, it was possible to find bacterial isolates like Aeromonas hydrophila which causes Bacterial Haemorrhagic Septicemic disease Disease of Cyprinus carpio [26]. Additionally, similar report from Eman et al [27] indicated Escherichia coli, Klebsiella pneumonia and Pseudomonas species are common bacterial isolates from Cyprinus carpio.…”
Section: Discussionmentioning
confidence: 89%
“…treatment A (67-68%), treatment B (69-77%), treatment C (75-83%), control (63-65%), can be seen in Figure 3. According to Parvez and Mudarris (2014), Cyprinus carpio fish infected with bacterial Hemorrhagic Septicemia (BHS), the number of lymphocytes is 39 % and after treatment with chloramphenicol the number of lymphocytes is 80%.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of bacterial attack on fish hatcheries can occur within a few hours. Bacterial attacks by A. salmonicida destroy the internal organs of fish fry and skin wounds (Parvez and Mudarris 2014;Alavinezhad et al 2021). The ability of A. salmonicida to infect fish is related to the bacteria's ability to produce toxins (Soni et al 2021).…”
Section: Introductionmentioning
confidence: 99%